TRANSLATION EQUIVALENCE OF SONG LYRICS FOR THE REST OF MY LIFE AND REFLECTION: (A Content Analysis Study) - Fauzi, Deri; Oktaviana, Fadilla; Amalia, Lia (Journal of English Language Teaching and Literature (JELTL), 2022)
This research focuses are to analyze the ttranslation equivalence and types of equivalence which occur in the song lyrics For the Rest of My Life and Reflection from English into Indonesian language. The writer uses documentation as the data of the research and uses content analysis as the research design. The result of research, as follows (1) For the song lyrics For The Rest of My Life, the meaning of equivalence with the different meaning category (FM) which is as much as 17 or 68%, there is no result value for rising meaning (RM) category, and for down meaning category (DM) as much as 6 or 24% appearances. Meanwhile, for non-equivalent, the missing meaning (MM) category as much as 1 or 4%; and for different meaning category (DM) as much as 17 or 68% appearances. Therefore, it can be concluded that the most appearance occurs on the different meaning (DM) category. (2) For the song lyrics Reflection, meaning of equivalence with the down meaning category (FM) which is as much as 15 or 51,7%, meanwhile there is no result value for full and rising meaning (RM) category. Meanwhile For non-equivalent, the missing meaning (MM) category as much as 1 or 3,4%, and for different meaning category (DM) as much as 13 or 44,8% appearances. Therefore, it can be concluded that the most appearance occurs on the down meaning (DM) category. In short, based on the data of analysis, either from the song lyrics For The Rest of my Life and Reflection then types of equivalence that occurs on the translation result on two the song are Dynamic Equivalence.